PENGARUH DANA ALOKASI UMUM DAN PENDAPATAN ASLI DAERAH TERHADAP BELANJA BARANG DAN JASA DENGAN BELANJA MODAL SEBAGAI VARIABEL INTERVENING: ( Studi pada Pemerintah Daerah Kabupaten/Kota di Provinsi Jawa Timur ) - Indra Wijayanto (STIE Mahardhika, 2021)
The goal of this research are to test the direct influence of General Allocation Found (DAU), Regional Original Income (PAD), and the indirect influence through Capital Expense as a intervening variable toward Product and Service Expense of Local Government East Java in 2019. This kind of research is a quantitative research, using classic assumption test for the examining research model, the multiple regression test for intervening variable test. The data of this research are the secondary data that is the APBD realization report year 2019 obtained from the website of the General Directorate of Financial Balance (www.djpk.depkeu.go.id). The number of research population is 38 districts/cities in East Java and of 33 districts/cities that meet the requirement to be the sample of research. The result of research shows that the General Allocation Found (DAU) and Regional Original Income (PAD) affect positively toward the Capital Expense, the Capital Expense affect positively toward the Product and Service Expense, and than General Allocation Found (DAU) that has the significant positive affect indirectly to the Product and Service Expense through the Capital Expense as the intervening variable. The result of this research expected can be input for government in making policy in the future.